Ion release, antimicrobial and physio-mechanical properties of glass ionomer cement containing micro or nanosized hexametaphosphate, and their effect on enamel demineralization - Hosida, Thayse Yumi [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Morais, Leonardo Antônio [UNESP]; Moraes, João Carlos Silos [UNESP]; Duque, Cristiane [UNESP]; Souza, José Antônio Santos [UNESP]; Pedrini, Denise [UNESP] (Springer Nature, 2019)
Objectives: To evaluate the effects of hexametaphosphate microparticles (mHMP) or nanoparticles (nHMP) incorporated in glass ionomer cement (GIC) on antimicrobial and physico-mechanical properties, fluoride (F) release, and enamel demineralization. Material and methods: HMP solutions were obtained at concentrations of 1, 3, 6, 9, and 12%, for screening of antimicrobial activity. Next, mHMP or nHMP at 6, 9, and 12% were incorporated into a resin-modified GIC and the antibacterial activity was evaluated. The resistance to diametral tensile and compressive strength, surface hardness, and degree of monomer conversion as well as F and HMP releases of GICs were determined. Furthermore, specimens were attached to enamel blocks and submitted to pH-cycling, and mineral loss was determined. Parametric and non-parametric tests were performed, after checking data homoscedasticity (p < 0.05). Results: HMP solutions at 6, 9, and 12% demonstrated the best antibacterial activity. GIC containing HMP showed better antibacterial effects at 9 and 12% for nHMP. Regarding F and HMP releases, the highest levels of release occurred for groups containing 9 and 12% nHMP. With the increase in HMP concentration, there was lower mineral loss. However, the incorporation of mHMP or nHMP in GIC reduced values of physico-mechanical properties when compared to the control GIC. Conclusions: nHMP improves antimicrobial activity and fluoride release, and decreases enamel demineralization, but reduces the physico-mechanical properties of GIC. Clinical relevance: The association of GIC/HMP could be an alternative material for patients at high risk for dental caries and could be indicated for low-stress regions or provisional restorations.
Keywords: Antibacterial agents; Compressive strength; Glass ionomer cements; Nanoparticles; Phosphates; Polymerization